SCADA Simulation of a Distributed Generation System with Storage Technologies. (2015) - Dulău, Lucian Ioan; Abrudean, Mihail; Bică, Dorin
Abstract: This paper describes the simulation of a distributed generation system with storage technologies. The simulation is performed using a SCADA software for a distributed generation system, considering the generation cost, the load and the availability of the system's generating units. Also, a storage unit is added to the system. An overview of the storage technologies is also presented.